2022
DOI: 10.3389/fcell.2022.894810
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-Mediated m6A RNA Methylation of ZBTB4 Interferes With Trophoblast Invasion and Maybe Involved in RSA

Abstract: N6-methyladenosine (m6A) was the most abundant modification of mRNA and lncRNA in mammalian cells and played an important role in many biological processes. However, whether m6A modification was associated with recurrent spontaneous abortion (RSA) and its roles were still unclear.Methods: Methylated RNA immunoprecipitation sequencing (MeRIP-Seq) was used to study the global m6A modification pattern in RSAs and controls. RNA sequencing (RNA-Seq) was used to study the level of global mRNA in two groups. Real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Li et al [14] found that the overexpression of ALKBH5 in embryonic villus tissues of RSA patients resulted in significantly decreased global mRNA m6A methylation, and proliferation and invasion of trophoblasts could be controlled via regulation of the half-life of CY R61 mRNA. Huang et al [15] found that the low expression of METTL3 protein in RSA embryonic villous tissues resulted in reduced m6A modification and stability of ZBTB4 RNA, which in turn affected the invasive capacity of trophoblasts. Zhao et al [16] found that ALKBH5 overexpression in the ESC line caused the hyposecretion of VEGF and subsequently impair macrophage recruitment and M2 differentiation, which could be the potential cause of RSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [14] found that the overexpression of ALKBH5 in embryonic villus tissues of RSA patients resulted in significantly decreased global mRNA m6A methylation, and proliferation and invasion of trophoblasts could be controlled via regulation of the half-life of CY R61 mRNA. Huang et al [15] found that the low expression of METTL3 protein in RSA embryonic villous tissues resulted in reduced m6A modification and stability of ZBTB4 RNA, which in turn affected the invasive capacity of trophoblasts. Zhao et al [16] found that ALKBH5 overexpression in the ESC line caused the hyposecretion of VEGF and subsequently impair macrophage recruitment and M2 differentiation, which could be the potential cause of RSA.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al . [15] found that the low expression of METTL3 protein in RSA embryonic villous tissues resulted in reduced m6A modification and stability of ZBTB4 RNA, which in turn affected the invasive capacity of trophoblasts. Zhao et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with the cellular response to DNA damage stimuli and negative regulation of RNA polymerase II transcription. Recently, the role of METTL3-mediated RNA methylation of m6ZBTB4 in trophoblastic invasion and recurrent spontaneous abortion (RSA) has been highlighted [ 54 ]. In addition, METTL3-mediated modification of m6ZBTB4 mRNA is also involved in smoking-induced EMT in lung cancer [ 55 ], Recent findings demonstrate a role for ZBTB4 in epigenetic regulation, particularly in DNA methylation, and its dysfunction has been implicated in recurrent spontaneous abortion and smoking-induced epithelial-to-mesenchymal transition in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Based on stromal gel invasion assay and transwell migration assays with METTL3 over-expressing and knockdown in HTR-8 cell lines, the reduction of METTL3-mediated m6A modification attenuated the attenuation of ZBTB4 and increased the expression of ZBTB4, thereby impairing the invasive ability of trophoblast cells. m6A modification in RNA is crucial for controlling trophoblast invasion ( 167 ). Another m6A methyltransferase, WTAP, promotes trophoblast invasion and metastasis by regulating the stability of HMGN3 mRNA in a m6A-dependent way ( 168 ).…”
Section: Rna Methylation In the Formation Of The Maternal-fetal Inter...mentioning
confidence: 99%